2019
DOI: 10.3390/nu11051076
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Modulation of Immune and Central Nervous System Homeostasis: The Role of Diet in Development of Neuroinflammation and Neurological Disease

Abstract: The gut-microbiome-brain axis is now recognized as an essential part in the regulation of systemic metabolism and homeostasis. Accumulating evidence has demonstrated that dietary patterns can influence the development of metabolic alterations and inflammation through the effects of nutrients on a multitude of variables, including microbiome composition, release of microbial products, gastrointestinal signaling molecules, and neurotransmitters. These signaling molecules are, in turn, implicated in the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 291 publications
1
37
0
1
Order By: Relevance
“…In adulthood, the composition of the intestinal microbiota is strongly dependent on factors such as long-term dietary patterns, antibiotic use, exercise, and psychological stress [5,10,24,25,34]. Because alterations in the intestinal microbiota have been linked to health and disease, many studies have examined ways to alter the microbiota composition through diet and supplementation [9].…”
Section: Modulating the Gastrointestinal Microbiota: The Effect Of Enmentioning
confidence: 99%
See 3 more Smart Citations
“…In adulthood, the composition of the intestinal microbiota is strongly dependent on factors such as long-term dietary patterns, antibiotic use, exercise, and psychological stress [5,10,24,25,34]. Because alterations in the intestinal microbiota have been linked to health and disease, many studies have examined ways to alter the microbiota composition through diet and supplementation [9].…”
Section: Modulating the Gastrointestinal Microbiota: The Effect Of Enmentioning
confidence: 99%
“…For example, the probiotic bacteria Lactobacilli and Bifidobacteria, among other strains, have been widely studied and have been shown to improve intestinal barrier function and prevent hyperpermeability via a variety of mechanisms including Toll-like recptor-2 mediated-immune-modulating and anti-inflammatory effects, by promoting the production of compounds that support intestinal barrier function, such as butyrate, and by eliciting positive structural changes in Zo-1 and occludin as part of the tight junction protein complexes [35]. Thus, they may also decrease transfer of LPS [5,36]. In addition, previous research suggests that probiotic bacteria may have a role in forming certain neuroactive compounds.…”
Section: Modulating the Gastrointestinal Microbiota: The Effect Of Enmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal flora imbalance caused by regularly consuming an unhealthful diet plays an important role in the occurrence and development of various diseases (Barrea et al 2018). Unhealthful eating habits can cause intestinal flora disorders, increasing intestinal permeability, forming chronic and low levels of inflammation, and further disrupting insulin signaling pathways, eventually leading to the onset of metabolic syndrome including insulin resistance, obesity, and diabetes (Avolio et al 2020;Dong et al 2019;Estrada and Contreras 2019;Saus et al 2019). Many studies have shown that marine dietary components can play a significant role in maintaining and promoting human health (Dong et al 2019).…”
Section: Intestinal Flora and Dietary Marine Ingredientsmentioning
confidence: 99%